Fast Software Encryption 20th International Workshop, FSE 2013, Singapore, March 11-13, 2013. Revised Selected Papers - Moriai, Shiho; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book constitutes the thoroughly refereed post-conference proceedings of the 20th International Workshop on Fast Software Encryption, held in Singapore, March 11-13, 2013. The 30 revised full papers presented were carefully reviewed and selected from 97 initial submissions. The papers are organized in topical sections on block ciphers, lightweight block ciphers, tweakable block ciphers, stream ciphers, hash functions, message authentication codes, provable security, implementation aspects, lightweight authenticated encryption, automated cryptanalysis, Boolean functions.
Block Ciphers -- Lightweight Block Ciphers -- Tweakable Block Ciphers -- Stream Ciphers -- Hash Functions -- Message Authentication Codes -- Provable Security -- Implementation Aspects -- Lightweight Authenticated Encryption -- Boolean Functions.
Keywords: Computer science; Computer security; Data encryption (Computer science).; Coding theory; Management information systems; Computer Science; Data Encryption; Systems and Data Security; Management of Computing and Information Systems; Coding and Information Theory; Electronic books